2009
DOI: 10.1073/pnas.0902204106
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular thiol-assisted selenium uptake dependent on the x c cystine transporter explains the cancer-specific cytotoxicity of selenite

Abstract: The selenium salt selenite (SeO3 2؊ ) is cytotoxic in low to moderate concentrations, with a remarkable specificity for cancer cells resistant to conventional chemotherapy. Our data show that selenium uptake and accumulation, rather than intracellular events, are crucial to the specific selenite cytotoxicity observed in resistant cancer cells. We show that selenium uptake depends on extracellular reduction, and that the extracellular environment is a key factor specific to selenite cytotoxicity. The extracellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
126
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(138 citation statements)
references
References 30 publications
10
126
2
Order By: Relevance
“…The possibility that SDG uptake would be increased by extracellular thiol compounds was suggested by a report proposing a mechanism for H 2 SeO 3 uptake assisted by extracellular thiols (Olm et al, 2009). However, instead, we found that SDG uptake was decreased by extracellular thiols.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…The possibility that SDG uptake would be increased by extracellular thiol compounds was suggested by a report proposing a mechanism for H 2 SeO 3 uptake assisted by extracellular thiols (Olm et al, 2009). However, instead, we found that SDG uptake was decreased by extracellular thiols.…”
Section: Discussioncontrasting
confidence: 55%
“…These results indicated that SDG is a preferable chemical form, over H 2 SeO 3, for cellular uptake of Se. Olm et al (2009) showed that reductive metabolism by extracellular thiol compounds increased selenite uptake in lung carcinoma cells. These investigators concluded that selenide is the important chemical form for Se uptake, but they did not consider SDG, which is formed during the production of selenide.…”
Section: Clear Advantages Of Sdg For Cellular Se Uptakementioning
confidence: 99%
See 1 more Smart Citation
“…The oxidoreductase thioredoxin (Trx) (11) is also up-regulated and involved in the redox remodeling after monocyte activation (8). Up-regulation of the cystine/cysteine redox cycle occurs and serves previously unrecognized signaling and homeostatic functions in different physiological and pathological responses (12), including antigen presentation (13), B cell differentiation (14), and, in cancer cells, resistance to apoptosis (9) and drug sensitivity (15).…”
mentioning
confidence: 99%
“…Moreover, the restoration of synaptic proteins, including synaptophysin and postsynaptic density protein 95 in the hippocampus and cortex, and inhibition of inflammatory response were observed in these mice treated with SeMet [130]. A recent study has shown the therapeutic effect of the novel organic Se compound p,p'-methoxyl-diphenyl diselenide (MeOPhSe) 2 against oxidative-nitrosative stress caused by ICV-STZ.…”
Section: Alzheimer's Diseasementioning
confidence: 99%